2017
DOI: 10.1039/c6tc04360g
|View full text |Cite
|
Sign up to set email alerts
|

Use of decomposable polymer-coated submicron Cu particles with effective additive for production of highly conductive Cu films at low sintering temperature

Abstract: A method for producing Cu films with low resistivity, based on low temperature sintering, is demonstrated. The Cu inks for preparing conductive Cu films consisted of Cu particles that were coated with a decomposable polymer (poly(propylenecarbonate), PPC) as well as a self-reducible copper formate/1-amino-2- propanol (CuF-IPA) complex as an additive. The sintering temperature used in this study was as low as 100 degrees C. Following sintering at a temperature of 100 degrees C, the lowest reported resistivity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Because the radiation energy is absorbed from top of copper film, the temperature on the top surface of the sintered thin films are higher than that of the substrate. Because the substrate temperature only increase slightly (~20 °C) [28,29,30,31] after IPL treatment, there exists a temperature difference ~300 °C between the sintered copper film and the substrate. As the result, the large thermal expansion difference between the copper film and the substrate leads to serious crack formation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the radiation energy is absorbed from top of copper film, the temperature on the top surface of the sintered thin films are higher than that of the substrate. Because the substrate temperature only increase slightly (~20 °C) [28,29,30,31] after IPL treatment, there exists a temperature difference ~300 °C between the sintered copper film and the substrate. As the result, the large thermal expansion difference between the copper film and the substrate leads to serious crack formation.…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, it has been found that cupric oxide coatings around copper nanoparticles can help particle connections in sintering process [14,27,28]. Moreover, a mixture of copper particles with various sizes are also found to be more efficient for particle fusion in the sintering process [29]. However, these experiments are performed in a nitrogen environment with a thermal sintering process.…”
Section: Introductionmentioning
confidence: 99%
“…Under the same experiment conditions (oven, sintering temperature and time, heating profile) and ink compositions, all samples can be considered having the same evaporation rate of IPA, thereby IPA evaporation rate is not the reason causing the significant difference in the resistivity of the sintered copper films. As reported for the sintering of copper particles/copper complex ink, the copper from the complex was generated and grew on the surface of added copper particles to form the final copper film2431. Low temperature sintering of copper particles without the metal complexes was also examined.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest resistivity of 32 μΩ cm was achieved using 0.4-μm Cu particles at a sintering temperature of 120 °C for 30 min under an N 2 atmosphere. They also prepared Cu particles (154 ± 54 nm in size) protected with an amine-decomposable polymer (poly(propylenecarbonate), PPC) and mixed the PPC-protected Cu particles and CuF–AmIP complex to achieve a low resistivity at low-temperature sintering under an N 2 atmosphere [ 135 ]. PPC can be decomposed into smaller molecules via an aminolysis reaction with AmIP.…”
Section: Formulation Designs In Cu-based Mixed Inks/pastesmentioning
confidence: 99%